The Influence of Perceived Organizational Support and Work Stress on Job Hopping Through Job Satisfaction as An Intervening Variable Among Gen Z Employees at Erafone Store Cirebon - Putri, Puane Pradipta; Anggara, Rehan; Solahudin, Ade (Syntax Corporation, 2025)
The tendency of employees to change jobs in a short time or job hopping is a concern in the world of work, especially among Generation Z. This study aims to analyze the effect of perceived organizational support (POS) and work stress on job hopping intentions with job satisfaction as an intervening variable in Generation Z employees at VeriFone Store Cirebon. Quantitative methods are used with testing using the Structural Equation Modeling (SEM) approach based on Smart PLS. Respondents in this study were Generation Z employees with a work period of less than two years. Data were collected through questionnaires with research instruments including the Job-Hopping Intention Scale (JHI), Survey of Perceived Organizational Support (SPOS-8), and Job Satisfaction scale. The results of the study indicate that perceived organizational support has a positive and significant effect on job satisfaction, while job stress has a negative effect on job satisfaction. In addition, job satisfaction is proven to be an intervening variable in the relationship between perceived organizational support, job stress, and job-hopping intentions. This study provides implications for companies in increasing organizational support and managing job stress in order to reduce the level of job hopping among Earphone Generation Z employees.